2003
DOI: 10.1038/sj.ejhg.5200993
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of the CTNS gene in Italy

Abstract: Classic nephropathic or infantile cystinosis (NC) is an autosomal recessive disorder; the gene coding for the integral membrane protein cystinosin, which is responsible for membrane transport of cystine (CTNS), was cloned. Mutation analysis of the CTNS gene of Caucasian patients revealed a common 57-kb deletion, and several other mutations spread throughout the entire gene. In the present study, we report the CTNS mutations identified in 42 of 46 Italian families with NC. The percentage of mutations characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Similarly, the studies performed in Italy and Turkey have reported that this mutation presented early indications and a slow course. 14,17 Consequently, upon comparison of the patients with cystinosis in this particular region with the European and North American patients, it is clear that different CTNS variants result in this disease. Sharing of some of the mutations between the Middle East countries and Turkey is likely due to the historical and geographical proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the studies performed in Italy and Turkey have reported that this mutation presented early indications and a slow course. 14,17 Consequently, upon comparison of the patients with cystinosis in this particular region with the European and North American patients, it is clear that different CTNS variants result in this disease. Sharing of some of the mutations between the Middle East countries and Turkey is likely due to the historical and geographical proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the small deletion c.809_811del; p. S270del was tested functionally and resulted in almost complete loss of function (Kalatzis et al 2004). The most widely distributed among the six previously reported mutations in Egyptian patients was c.1015G>A; p. G339R, as it was reported in Turkey (Topaloglu et al 2012), Italy (Mason et al 2003), Germany (Kiehntopf et al 2002), France (Attard et al 1999), Spain (Macías-Vidal et al 2009), the USA (Shotelersuk et al 1998), and Canada (Rupar et al 2001), followed by c.922G>A; p.G308R reported in Saudi Arabia (Aldahmesh et al 2009), Italy (Mason et al 2003), France (Attard et al 1999), Spain (Macías-Vidal et al 2009), and the USA (Shotelersuk et al 1998). The mutation c.809_811del; p.S270del was also relatively widespread, as it was reported in France (Attard et al 1999) and India (Tang et al 2009) (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…A single study in the Far East (Thailand) also reported the absence of the 57-kb mutant allele in six patients of Thai and Cambodian origins (Yeetong et al 2012). Apparently, this common mutation is restricted to the Northern European/American populations and, to a lesser extent, to countries of possible genetic contact as in Italy (Mason et al 2003) and Mexico (AlcÄntara-Ortigoza et al 2008). This supports the theory that this founder mutation originated very recently during human evolution, perhaps less than 2,000 years ago somewhere in Northern Europe (Kalatzis and Antignac 2002); so it has not got the chance to spread to remote ethnicities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…N C (MIM 219800) is an autosomal recessive disorder characterized by impaired lysosomal transport of cystine (1) and caused by mutations or deletions of the lysosomal amino acid carrier cystinosin (CTNS), encoded by the CTNS gene (17p13) (2,3).…”
mentioning
confidence: 99%